2009
DOI: 10.1186/1476-511x-8-21
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid bacteria affect serum cholesterol levels, harmful fecal enzyme activity, and fecal water content

Abstract: BackgroundLactic acid bacteria (LAB) are beneficial probiotic organisms that contribute to improved nutrition, microbial balance, and immuno-enhancement of the intestinal tract, as well as lower cholesterol. Although present in many foods, most trials have been in spreads or dairy products. Here we tested whether Bifidobacteria isolates could lower cholesterol, inhibit harmful enzyme activities, and control fecal water content.MethodsIn vitro culture experiments were performed to evaluate the ability of Bifido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 55 publications
3
62
0
1
Order By: Relevance
“…This is complement with Loh et al (2009) when they reported that feeding 0.25% spray-dried metabolite was able to reduce the plasma cholesterol concentration in postweaning rats. Fermented milk containing L. acidophilus L1 had effects in reducing 2.4-3.2% of serum cholesterol concentration in human (Lee et al, 2009). The effect of LAB on lipid content may be due to enhance the bile salt hydrolase (BSH) activity and facilitate the elimination of cholesterol in faeces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is complement with Loh et al (2009) when they reported that feeding 0.25% spray-dried metabolite was able to reduce the plasma cholesterol concentration in postweaning rats. Fermented milk containing L. acidophilus L1 had effects in reducing 2.4-3.2% of serum cholesterol concentration in human (Lee et al, 2009). The effect of LAB on lipid content may be due to enhance the bile salt hydrolase (BSH) activity and facilitate the elimination of cholesterol in faeces.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that LAB able to reduce plasma cholesterol when used as an additive in animal feeding (Sindhu and Khetarpaul, 2003;Loh et al, 2009). Lee et al (2009) showed Lactobacillus plantarum could reduce the plasma cholesterol. Foo et al (2003) also reported that Lactobacillus cultures from fermented products decreased plasma cholesterol concentration in rats.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that bifidobacteria is beneficial for humans, and 96 cases in the literature on the cholesterol-lowering effect of bifidobacteria or other prebiotics (key words: bifidobacteria, cholesterol) were obtained in PubMed (41). When we determined neutral sugar from AE, xylose was observed (2.560.6 mg/g of dry matter).…”
Section: Discussionmentioning
confidence: 99%
“…Usman and Hosono [10] also observed a significant reduction in TC and LDL-C in rats fed L. gasseri. In a more recent study, B. longum SPM1207 isolated from healthy adult Koreans reduced serum TC and LDL-C significantly (p <0.05), and slightly increased serum HDL-C in rats [11]. In another study, Shin et al [10] demonstrated that B. longum SPM1207, although killed by sonication, could significantly reduce serum TC and LDL-C, but with no significant improvement in HDL-C when fed to rats for 3 weeks [66].…”
Section: Hypocholesterolaemic Effects Of Probioticsmentioning
confidence: 99%
“…Probiotics are beneficial bacteria that influence the health of the host by improving their microbial balance. Modifications of intestinal flora have been shown to be beneficial on lipid metabolism in mice [2][3][4][5][6], rats [7][8][9][10][11], guinea pigs [12] and pigs [13]. In contrast, studies in humans [14,15] indicated that the role of fermented milk products as hypocholesterolaemic agents were inconsistent but more reliable effects were documented in the recent clinical studies [16][17][18][19].…”
Section: Introductionmentioning
confidence: 95%